Pendekatan Baru Maqasid al-Shariah Dalam Pengajian Syariah di Malaysia: Satu Analisis - Rahim, R.A.A.; Ismail, P.; Awang, I. (2006)
The article attempts to forward a holistic approach of Maqasid of al-shariah in Shariah Studies in Malaysia. The proposal is based on the belief that the concept of Maqasid al-Shariah as well as its application has its own significance in the programming of Shariah Studies in Malaysia. The discussion begins by introducing the essentiality of Maqasid al-Shariah, the needs in the process of globalization and their relevance in Maqasid al- Shariah, and an analysis of the proposed approach as implemented in the Shariah Studies at the Academy of Islamic Studies, University of Malaya.